Development of a nano-targeting chimera for the degradation of membrane and cytoplasmic proteins - Jin, Peipei; Chen, Zhaozheng; Zhang, Ju; Li, Haowen; Wei, Pengfei; Wang, Ziyu; Feng, Qiyu; Wang, Hongyang; Han, Da; Miao, Yanyan (Acta biomaterialia, 2025)
Various targeted protein degradation (TPD) approaches have been developed to overcome the limitations of traditional drug in eliminating pathogenic proteins by exploiting either the proteasomal or lysosomal pathway. However, there is still a lack of design strategies for TPD that utilize two distinct pathways to achieve the degradation of membrane and cytoplasmic proteins. Here, we develop a Nano-Targeting Chimera (Nano-APTAC), which is engineered by covalently attaching the protein-targeting aptamer to graphene oxide (GO) via the amide linkage, to hijack the autophagy-lysosome and ubiquitin-proteasome systems for targeted degradation of membrane and cytoplasmic proteins respectively. In contrast, a mixture of GO and aptamers without covalent interaction has no effect on protein degradation. Furthermore, the in vivo experiments demonstrate the efficacy of Nano-APTACs in depleting targeted proteins and inhibiting tumor growth. The work provides a versatile programmability platform, employing two distinct degradation systems to facilitate personalized design for the degradation of proteins regardless of their localization on the membrane or cytoplasm, and offering potential therapeutic benefits. GO and aptamers have been combined for various applications. However, the utilization of this combination in TPD remains unknown. In this study, we found that the Nano-APTAC platform, constructed by covalently linking GO-aptamer chimera (not a simple mixture), can utilize autophagy-lysosome system and ubiquitin-proteasome system to degrade membrane and cytoplasmic proteins, respectively. The types of aptamers significantly influence the intracellular behavior of the chimeras, resulting in distinct subcellular localization and guiding the chimera to select specific degradation systems for protein removal. The Nano-APTAC's mode of action extremely expands the range of targeted proteins, prevents overload in specific degradation systems caused by excessive usage, and provides an exceptional level of adaptability in meeting diverse treatment requirements. [Display omitted]